2015
DOI: 10.1111/bjet.12249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mathematics computer games on special education students' multiplicative reasoning ability

Abstract: This study examined the effects of a teacher-delivered intervention with online mathematics mini-games on special education students' multiplicative reasoning ability (multiplication and division). The games involved declarative, procedural, as well as conceptual knowledge of multiplicative relations, and were accompanied with teacherled lessons and class discussions. A pretest-posttest control-group design was employed, with 81 students from five schools for special primary education (three experimental schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…It is very important to emphasize that this study was conducted to students in early childhood, a field of increasing research interest with, however, a limited research body. Existing studies in this field have highlighted the potential of working with children in the design of new technologies (Allsop, ; Bakker et al ., ; Khaled & Vasalou, ; Lameras et al ., ; Yip et al ., ) and have highlighted several challenges. The present study offers more empirical data that supports the argument that facilitating game design sessions with children in early childhood has a positive impact on their game design and problem posing skills and highlights the potential of conducting additional research towards this direction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to emphasize that this study was conducted to students in early childhood, a field of increasing research interest with, however, a limited research body. Existing studies in this field have highlighted the potential of working with children in the design of new technologies (Allsop, ; Bakker et al ., ; Khaled & Vasalou, ; Lameras et al ., ; Yip et al ., ) and have highlighted several challenges. The present study offers more empirical data that supports the argument that facilitating game design sessions with children in early childhood has a positive impact on their game design and problem posing skills and highlights the potential of conducting additional research towards this direction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When it comes to game design and its connection to mathematics education, research interest can be categorized in three axis: The first one is related to the impact of playing games on students' cognitive skills (Bakker, van den Heuvel-Panhuizen, & Robitzsch, 2016;Kebritchi, Hirumi, & Bai, 2010), the second one is related to the impact of designing games on students' mathematical thinking (Kafai, 2006;Ke, 2014), while the third one is related to the development and application of skills and competences related to game design as a craft of its own (Moser et al, 2014). Designing games with early childhood students has proved a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Serious games proved to be an especially great tool when it comes to general problem-solving skills [17], language learning [18][19][20], history and physical education [20] as well as science education [18,21,22]. Games have also been researched in special needs education students and research showed that using serious games in education enhances students' cognitive outcomes as well as social behavior [23][24][25].…”
Section: Using Games As a Teaching Tool: An Overview Of Advantages Anmentioning
confidence: 99%
“…A number of visual materials are used in the concept teaching. The use of different materials in the education of students with mental disorders makes the education be more easier as well as contribute to the permanence of information (Hwang, Su, Huang & Dong, 2009;Bakker, Heuvel-Panhuizen, & Robitzsch, 2016).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%